Block-based motion estimation algorithms — a survey - Jakubowski, M.; Pastuszak, G. (Opto-electronics review, 2013)
In the multi-view video coding, both temporal and inter-view redundancies can be exploited by using standard block-based motion estimation (BBME) technique. In this paper, an extensive review of BBME algorithms proposed within the last three decades is presented. Algorithms are divided into five categories: 1) based on the search position number reduction; 2) multiresolution; 3) based on the simplification of matching criterion; 4) fast full search; 5) computation-aware. Algorithms are compared in terms of their efficiency and computational complexity.